Ethnicity, class, and civil war: the role of hierarchy, segmentation, and cross-cutting cleavages. Issue 1 (2nd January 2016) - Siroky, David; Hechter, Michael
Abstract: Why are some countries prone to ethno-nationalist conflict, whereas others are plagued by class conflict? This is a question that has seldom been raised and rarely been examined empirically. This paper presents a social-structural theory to account for the variable incidence of these two forms of political instability. These two types of conflict result from distinct principles of group solidarity – ethnicity and class – and since each individual is simultaneously a member of an ethnic group (or many such groups) and a particular class, these two principles vary in the degree to which they are mutually exclusive or cross-cutting. The degree of economic stratification between groups and economic segmentation within them shapes the relative salience of each principle of group solidarity in any society and is associated with a characteristic form of political mobilization. In places where between-group inequalities are high, and within-group inequalities low, ethnicity should be the dominant principle of group solidarity and serve as the primary basis of group conflict. By contrast, in countries where between-group inequalities are low, and within-group inequalities high, class is more likely to serve as the dominant principle of group solidarity, and conflicts along class lines are more likely. We test these conjectures with data in over 100 countries on cross-cutting cleavages, ethnic war, and class conflict. The results are supportive of the theory, and provide evidence that how groups are stratified and segmented in societies shapes the type of civil war.